Non-Invasive Electrochemical Biosensors for TNF-α Cytokines Detection in Body Fluids - Lu, Yang; Zhou, Qingqing; Xu, Lin (Frontiers in Bioengineering and Biotechnology, 2021)
Determining pro-inflammatory cytokine tumor necrosis factor-alpha (TNF-α), which is an important indicator in early cardiac dysfunction and subsequent heart failure, have received increasing attention recently, due to the appealing characteristics of TNF-α such as easy to extract from body fluid, may serve as the early sign of inflammation, and etc. Considering rapidity of the heart disease progression, developing fast, simple, and friendly detection method to quantify the concentration of TNF-α beyond conventionality of the biochemical assays is quiet essential. Saliva, tear and urine, which can be sampled in a non-invasive way, are considered to be an important matrix for monitoring and assessing physiological status of human beings, importantly they also provide an ideal windows for monitoring the concentration of TNF-α. As a fast, accurate, cheap, portable and scalable method, electrochemical biosensors is very promising for biomarker detection in the matrix that obtained in a non-invasive way. This review summarized and compared the electrochemical biosensors for the detection of TNF-α in a non-invasive way, and highlights recent advance, and future prospects in developing high performance electrochemical platforms for noninvasive determination of TNF-α.